“Living with” CACNA1A-related hemiplegic migraine, a disease concept model - Schaare, Donna; Allison, Kendra; Skorge, Kara; Fox, Pangkong; Lusk, Laina; Sarasua, Sara M.; Helbig, Ingo; Boccuto, Luigi (Frontiers in Neurology, 2024)
IntroductionCACNA1A-related Hemiplegic Migraine (HM) is a rare neurological disorder distinguished by paroxysmal episodes of hemiparesis/hemiplegia with and without headache. Clinical features have been widely characterized, yet the impacts of the paroxysmal events on the patient and caregiver have not been thoroughly explored. Disease concept models are formal frameworks used to describe the lived experiences of patients and their families, offering a source for surrogate endpoints for clinical trials.MethodsWe completed 13 semi-structured interviews with caregivers of 12 individuals diagnosed with CACNA1A-related HM. We methodically coded themes, grouping concepts into three domains. We measured the occurrence of concepts throughout all interviews and subgroups stratified by age categories.ResultsOver 11 h of interviews yielded 2,018 references to 27 distinct concepts. Established symptoms such as seizures (87 references; including status epilepticus 27 references), hemiparesis/hemiplegia (24 references), and unconsciousness (17 references) were referenced, as well as previously underreported symptoms such as apneic episodes (32 references), lost ability to eat (13 references), and vascular access challenges (10 references). The symptom impacts were largely medical (294 references), followed by health (101 references), emotional (36 references), daily living (28 references), and social (26 references). Caregiver impacts were the most referenced domain (995 references), with the pivotal effects seen in caregiver requirements (355 references), emotional (245 references), HM treatments (179 references), daily living (148 references), and health support (135 references).DiscussionCACNA1A-related HM is a complex disorder defined by serious paroxysmal events that affects a broad range of social and clinical domains. We systematically classified symptoms and impacts from HM episodes, creating a disease concept model to help develop surrogate endpoints for future clinical trials, and identified two opportunities to improve patient management, including a written emergency protocol and a transition plan for adolescents approaching adulthood.